2002
DOI: 10.1046/j.1468-8123.2002.00031.x
|View full text |Cite
|
Sign up to set email alerts
|

Gas breakthrough experiments on fine‐grained sedimentary rocks

Abstract: The capillary sealing efficiency of fine‐grained sedimentary rocks has been investigated by gas breakthrough experiments on fully water saturated claystones and siltstones (Boom Clay from Belgium, Opalinus Clay from Switzerland and Tertiary mudstone from offshore Norway) of different lithological compositions. Sand contents of the samples were consistently below 12%, major clay minerals were illite and smectite. Porosities determined by mercury injection lay between 10 and 30% while specific surface areas dete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
252
1
4

Year Published

2007
2007
2018
2018

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 293 publications
(265 citation statements)
references
References 17 publications
(57 reference statements)
8
252
1
4
Order By: Relevance
“…A two-phase fluid flow drainage process is induced through the rock sample in a triaxial cell, which reproduces the in situ confining pressure and stress conditions acting on the rock [10]. The test can be performed and interpreted according to different experimental procedures and approaches [11][12][13]; generally, mercury-air or nitrogen-water systems are utilized in lab experiments and the results are then corrected according to the real gas-water characteristics.…”
Section: Threshold Pressurementioning
confidence: 99%
“…A two-phase fluid flow drainage process is induced through the rock sample in a triaxial cell, which reproduces the in situ confining pressure and stress conditions acting on the rock [10]. The test can be performed and interpreted according to different experimental procedures and approaches [11][12][13]; generally, mercury-air or nitrogen-water systems are utilized in lab experiments and the results are then corrected according to the real gas-water characteristics.…”
Section: Threshold Pressurementioning
confidence: 99%
“…As discussed in Section 3.2.2.3, seal permeability may vary in a wide range from approximately 10 -16 to 10 -23 m 2 (Neuzil, 1994;Hildenbrand et al, 2002Hildenbrand et al, , 2003Hart et al, 2006). Capillarity also plays an important role in trapping CO 2 under a caprock unit because CO 2 , as a non-wetting phase in a saline aquifer, can migrate into the seals only when the pressure buildup in the storage formation is higher than the capillary entry pressure in a CO 2 -brine system.…”
Section: Background On the Role Of Seals And Seal Propertiesmentioning
confidence: 99%
“…The capillary-barrier role of the confining units depends on the contrast of the pressure buildup in the storage formation and the entry pressure of the seals. Confining layers may have a wide range of entry pressures, as measured through laboratory CO 2 -breakthrough experiments (Hildenbrand et al, 2002(Hildenbrand et al, , 2003Li et al, 2005). For example, Hildenbrand et al (2002Hildenbrand et al ( , 2003 reported capillary displacement pressure for CO 2 -brine systems varying from 1 bar to 49 bar.…”
Section: Background On the Role Of Seals And Seal Propertiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Sealing capacity features essentially two parameters: displacement pressure, which begins infiltration of the gas phase into the initially water (brine) saturated pore system of the sealing rock, and the relative permeability to gas phase after the gas breakthrough (Hildenbrand et al, 2002). Relative permeability is a function of the gas/water saturation of the pore system, which is not easy to determine if fine-grained rocks.…”
Section: Introductionmentioning
confidence: 99%